Impacts of government and market on firm's efforts to reduce pollution - Bowon Kim; Jeong Eun Sim (Cogent Economics & Finance, 2015)
We examine how the government and the market affect firm's pollution abatement efforts, i.e. firm's efforts to reduce its pollution emission. The way for the government to control firm's pollution is to impose penalty, whereas the consumers (the market) make their purchasing decision by taking into account the pollution, i.e. the demand is affected by the stock of pollution. In effect, we consider two forces, government penalty and consumer's sensitivity to pollution, as primary factors to control firm's pollution and analyze their interaction in relation to the firm's pollution reduction efforts. The analysis suggests as follows. The government penalty and the consumer's awareness are substitutes either (1) when the market size is relatively large or (2) when the market is relatively small, but the government penalty is relatively heavy. On the contrary, the two factors are complements when the market size is relatively small and the government penalty is relatively light. We discuss managerial and economic implications of the analysis results.
Keywords: 330; pollution reduction; government penalty; consumer awareness